2022
DOI: 10.3390/fermentation8120697
|View full text |Cite
|
Sign up to set email alerts
|

Development of Probiotic-Fermented Black Mulberry (Morus nigra L.) Juice and Its Antioxidant Activity in C2C12 Cells

Abstract: Black mulberry (Morus nigra L.) is considered a medicinal and food-homologous plant in China. An obstacle to its widespread use is that its annual season and shelf life are extremely short. In this paper, fermented black mulberry juice (FBMJ) was prepared with various probiotic strains, and response surface methodology was used to determine the optimum production conditions for achieving the maximum active substance content in the resulting product. The fermentation process increased levels of biological enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…For these results, the differences are due to the unique properties of each strain resulting in fermented samples with different acidic flavors and different organic acid compositions that give each sample a unique flavor. Besides, the volatile compound composition of the FTJ varies from strain to strain, and the senses will be different ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…For these results, the differences are due to the unique properties of each strain resulting in fermented samples with different acidic flavors and different organic acid compositions that give each sample a unique flavor. Besides, the volatile compound composition of the FTJ varies from strain to strain, and the senses will be different ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the activity of fermented MFH was evaluated from a nonenzymatic antioxidant perspective. Lv et al evaluated the protective effect of fermented black mulberry juice against H 2 O 2 -induced oxidative stress in C 2 C 12 cells and showed an increase in superoxide dismutase activity and glutathione peroxidase levels, as well as a decrease in reactive oxygen species levels and malondialdehyde content after 24 h of fermented mulberry treatment (Lv et al, 2022). The other study reported the effect of fermented Coix seed on H 2 O 2 -induced oxidative stress in HSF cells.…”
Section: Anti-oxidative Activitiesmentioning
confidence: 99%
“…Probiotic fermentation improves the nutritional value of feed by increasing the content of amino acids, fatty acids, flavor substances, biological enzyme activities, probiotics and their secreted products such as exoenzymes, vitamins, and various SCFA, thereby improving digestive, absorptive, and immunity function in pigs (Hao et al, 2020). It is found that the content of crude protein, essential amino acids, flavor amino acids, and flavonoids, as well as unsaturated fatty acids after fermentation was significantly increased, while the content of saturated fatty acids (SFAs) was significantly reduced (Lv et al, 2023; Mohammadi & Ostovar, 2023), which may be main contributors to the improved meat quality (Debi et al, 2022; Lan et al, 2023; Wang, Sun, et al, 2023; Zhao et al, 2023).…”
Section: Effects Of Fermentation On the Improvement Of Feed Qualitymentioning
confidence: 99%
“…Feed supplementation, especially the fermented feed plays a key role in the regulation of pork nutritional quality. It was found that the content of crude protein, amino acids (especially aromatic amino acids), IMF, and fatty acids in the longissimus dorsi muscle was significantly increased after feeding finishing pigs with several kinds of fermented feed using different raw materials and probiotics (Dias et al, 2023; Lv et al, 2023; Mohammadi & Ostovar, 2023; Morgan et al, 2022; Shuai et al, 2023; Zhang, Wei, et al, 2022).…”
Section: Effects and Regulatory Mechanism Of Fermented Feed On Pork Q...mentioning
confidence: 99%